2011
DOI: 10.1016/j.actbio.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of photocrosslinkable gelatin and silk fibroin interpenetrating polymer network hydrogels

Abstract: To effectively repair or replace damaged tissues, it is necessary to design scaffolds with tunable structural and biomechanical properties that closely mimic the host tissue. In this paper, we describe a newly synthesized photocrosslinkable interpenetrating polymer network (IPN) hydrogel based on gelatin methacrylate (GelMA) and silk fibroin (SF) formed by sequential polymerization, which possesses tunable structural and biological properties. Experimental results revealed that IPNs, where both the GelMA and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
214
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(227 citation statements)
references
References 57 publications
11
214
1
1
Order By: Relevance
“…Hydrogels have received a considerable attention for use in tissue engineering scaffolds (with gelatin methacrylamide/PEG [72], silk fibroin/poly(vinyl alcohol) [73], silk fibroin/gelatin [74] or others [75]), cartilage tissue engineering (with poly (ethylene glycol)/agarose [76]), vascular tissue engineering (dextran/gelatin [77]). Mechanically enhanced properties (e.g., Young's moduli) rivaling those of natural load-bearing tissues was found in a poly (acrylic acid)/end-linked poly (ethylene glycol) crosslinked material [78].…”
Section: Examples Of Final Properties For Photochemically Produced Ipnsmentioning
confidence: 99%
“…Hydrogels have received a considerable attention for use in tissue engineering scaffolds (with gelatin methacrylamide/PEG [72], silk fibroin/poly(vinyl alcohol) [73], silk fibroin/gelatin [74] or others [75]), cartilage tissue engineering (with poly (ethylene glycol)/agarose [76]), vascular tissue engineering (dextran/gelatin [77]). Mechanically enhanced properties (e.g., Young's moduli) rivaling those of natural load-bearing tissues was found in a poly (acrylic acid)/end-linked poly (ethylene glycol) crosslinked material [78].…”
Section: Examples Of Final Properties For Photochemically Produced Ipnsmentioning
confidence: 99%
“…Through reviewing research articles about B. mori SF hydrogels, we found that the gelation time of SF hydrogels is excessively long unless nonphysiological treatments (such as low pH, high temperature, or additives) are considered [6,[13][14][15][16][17]. The question we want to answer is do the A. pernyi SF hydrogels have a similar problem?…”
Section: Introductionmentioning
confidence: 99%
“…These GelMA-SF IPN hydrogels have higher Young's modulus and are resistant to collagenase digestion. In addition, by varying GelMa and SF ratio, the IPN hydrogels' structural and biophysical properties can be tuned [81] .…”
Section: Photocrosslinkable Hydrogelmentioning
confidence: 99%